DEVELOPMENT AND VALIDATION OF NURSING CONSULTATION FOR PEOPLE WITH DIABETIC FOOT IN PRIMARY CARE - Caldeira, Joyce Micaelle Alves; Mendes, João Batista; Lacerda, Allysson Steve Mota; Brito, Maria Fernanda Santos Figueiredo; Caldeira, Antônio Prates; Evangelista, Christiane Borges; Araújo, Diego Dias de (Cogitare Enfermagem, 2024)
Objective: Develop and validate a nursing consultation instrument for people with diabetic foot in primary health care, based on Wanda de Aguiar Horta’s theoretical model of Basic Human Needs. Method: Methodological study, conducted from October 2022 to June 2023 in Montes Claros - Minas Gerais - Brazil, in three stages: scoping review to identify sociodemographic, clinical characteristics, and psychobiological, psychosocial, and psycho-spiritual needs; development of the instrument and content validation by experts. Descriptive statistics and a Content Validity Index equal to or greater than 0.80 were used for data analysis. Results: Content validation was performed by 15 experts. Three items of the instrument were evaluated, obtaining a Content Validity Index of 0.93 in objectives, 0.97 in structure and presentation, and 1.00 in relevance. Conclusion: The instrument will contribute to the qualification of nursing consultation for people with diabetic foot in primary health care.